Study of glass-steel interface for corrosion resistant applications - Kaur, Bhupinder (My University, 2013)
Glass is an amorphous (non-crystalline) solid material. Glasses are typically brittle and optically transparent. The most familiar type of glass used since centuries in windows and drinking vessels is soda-lime glass. Glass and glass-ceramics are assuming increasing importance in different industries including the medical, dental, chemical, communications, aerospace, and nuclear fields. However, if coated on metallic substances they can provide good corrosion resistance with support of metallic core provided the coating is stable. One of the major applications of these coating could be for the components used in underwater pathway. The resistance offered by glass surface in different corrosive environment particularly in aqueous solution is of great practical significance. Thus, it is essential to know the surface chemistry of different glasses in order to optimize their performance. In general terms the durability of glass may be defined as resistance of the glass surface to corrosion, i.e., chemical or physical changes caused by interaction with the environment. Consequently, durability of glass is a function of glass composition and surface state as well as the corrosive conditions of the environment. Stability of glasses depends upon various factors that include specifications of physical state, shape, surface condition as well as their physicochemical data in different corroding media which depends upon the mode of corrosion, and method of their evaluation. These are the primary objectives for choosing a glass–ceramic coating against all other types of available coating materials. Glass coating on metallic substance may be useful to manufacturing industries as it may lead to development of heat and corrosion resistant material. A strong joining of two materials depends on chemical and physical factors of the interfaces. The combination of transparency and hardness at room temperature along with sufficient strength and excellent corrosion resistant to different environments make glass indispensable. The high chemical resistance offered by glass coating may provide good corrosion resistant and higher life to steel. Generally passive films, conversion coatings, metallic and organic coatings confer corrosion protection via a variety of mechanisms, including formation of barriers to the penetration of corrodants, high ionic resistivity in surface layers to minimize electrochemical reactions under the coating at the metal–coating interface and presence of active corrosion inhibitiors. As glasses are chemically inert inorganic xxv substances, the coating of glasses can provide better corrosion protection at the interface. The present work deals with the synthesis, characterization and compatibility of (60-x) SiO2 -10 Al2O3-5 TiO2-15 CaO- (10+x) Na2O (x= 0, 5, 10 and 15) glasses with crofer, duplex, HSLA and stainless steel (SS). The entire work in this thesis is presented in five chapters. Chapter 1 gives description about glasses, their classification based on constituents used and various structural models for different glasses. Further the application of glass as a promising candidate for coating application on steel has been discussed. Detail description of corrosion, particularly in marine environment for both steel structures and glasses has been discussed. The various ways of corrosion protection of steels have been described. It also elaborates the reason for selecting glass as a coating material on steel over others materials as a corrosion resistant coat. Chapter 2 describes the literature details on glass corrosion, steel corrosion and glass-steel interaction study. Corrosion of glasses in different environment leads to development of different product. These have also been reviewed with aim to correlate it with the present work. The corrosion behavior of glasses at glass-steel interface is influenced by type of steel used as a substrate. The role of different glass formers, modifiers and additives which provide good interfacial bonding is also described as these influence the glass transition temperature, viscosity and diffusivity for having good wettability. The literature work of those categories of papers which are relevant to present study is presented here. Chapter 3 describes the experimental procedures followed to prepare glasses of different compositions, the specifications of different steels used and procedure adopted to prepare diffusion couple from these materials. Further the preparation of working electrode, cell and testing solution for corrosion testing is also documented. The characterization procedures along with instrument’s details, working and operating conditions have been given. Chapter 4 describes the results into three sections. First section contains the results of glasses obtained by Differential Thermal Analysis (DTA), Thermal Dilatometric Analysis (TDA), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) with Energy Dispersive Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR), UV-Visible and dielectric measurement of the glass samples are analyzed and discussed. The xxvi entire work has been done to achieve the properties of glasses which can make it suitable as glass coating material on steel. The properties which are required for making the glass suitable for coating are glass transition temperature (Tg), crystallization temperature (Tc) and thermal expansion coefficient (TEC). The second section gives information on important aspect of glass interaction with steels. The interaction study of glasses with crofer, duplex, HSLA and SS is described. For this study, glass powder of N-series and commercial glasses was coated by slurry method on steel and heated at 900 °C and 700 °C for 1 h, respectively. The top glass surface as well as the interface was analyzed under scanning electron microscope with EDS. The third section presents the corrosion study of glasses, steels and diffusion couples. Corrosion studies of N-series glasses followed by their characterization using XRD, FTIR and ICP methods. The electrochemical testing of N-series glasses is described as it is a critical study to check the dissolution characteristic of glasses in varieties of aqueous solution. Corrosion study of steels is essential to know the nature of corrosion including pitting that takes place in present experimental set-up. Though data on steels are available but not for the acquired laboratory set-up where all materials are tested under similar environment. The electrochemical study of, best diffusion couples is investigated for varied time period of short to long time. These diffusion couples are characterized by SEM with EDS after corrosion to have a better understanding from industrial point of view. Chapter 5 presents the overall conclusion of entire work and suggestion for future work.
Doctor of Philosophy, Thesis
Keywords: Glasses; Interface; Thermal properties; Corrosion